AB0691 CHARACTERIZATION OF DIFFERENT GROUPS WITH IMAGING AND NON-IMAGING FINDINGS OF ANKYLOSING SPONDYLITIS COMBINE WITH HIP LESION IN WESTERN CHINESE. (2nd June 2020) - Han, Q.; Zheng, Z.; Zhang, K.; Yu, Z.; Yang, F.; Liang, Q.; Zhu, P.; Baraliakos, X.
Abstract : Background: Hip joint lesion are the main cause of disability in patients with Ankylosing Spondylitis(AS) in western China. Seriously affect the quality of life of patients.The early clinical characteristics of hip joint disease are not typical, the disease is insidious, and the radiological diagnosis is delayed.The main prevention is early screening and early diagnosis. Objectives: This study attempted to find out the main characteristics and related factors in different groups of AS combine with hip joint lesion in western China. Methods: A-First evaluation: How many patients have 1) active SIJ changes on MRI. 2) chronic SIJ changes (each for erosion, clerosis, ankylosis, or any of those) on MRI. 3) a combination of active changes and chronic changes (each for erosion, sclerosis, ankylosis, or any of those) on MRI. 4) active hip changes on MRI. 5) chonic hip changes (erosion, effusion any of those) on MRI. 6) a combination of active changes and chronic hanges (erosion, effusion any of those) on MRI. B-Then, combination SIJ / hip. 7) active SIJ changes on MRI and in parallel active hip changes on MRI. 8) chronic (see above) SIJ changes on MRI and in parallel active hip changes on MRI. 9) chronic (see above) SIJ changes on MRI and in parallel chronic (see above) hip changes on MRI. 10) chronic (see above) SIJ changes on MRI and in parallel any (active or chronic) hip changes on MRI. C-Then, characterization of these groups with non-imaging findings. Characteristics of groups 7-10 above, for age, sex, Disease duration, Hip pain, Joint pain, enthesitis, Diarrhea, uveitis, ASDAS-CRP, BASDAI, BASFI, BASMI, Pat. Global, CRP, ESR, Harris Score, HLA-B27. Results: Retrospective analysis total 558 SpA patients (mean age 29, mean duration 5 years). 1) HIP-Active+Chronic group (N=288, AS=151) vs SIJ+HIP-Active group (N=241, AS=138): hip pain (p<0.0001), diarrhea (p<0.0001), joint pain (p<0.0001) and BASFI (p<0.05); 2) HIP-Active+Chronic(N=117, AS=58) vs SIJ-Chronic+HIP-Active group (N=214, AS=134): hip pain(p<0.0001), joint pain (p<0.0001), enthesitis (p<0.0001), ASDAS-CRP (p<0.05) and ESR (p<0.05); 3) SIJ-Active+Chronic group (N=204, AS=125) vs SIJ-Chronic+HIP-Active group (N=214, AS=134): hip pain (p<0.0001), joint pain (p<0.0001); 4) SIJ-Active+Chronic group (N=204, AS=125) vs SIJ+HIP-Chronic group (N=72, AS=40):hip pain (p<0.0001), Pat. Global (p<0.05); 5) SIJ+HIP-Active group (N=241, AS=138) vs SIJ-Chronic+HIP-Active group (N=214, AS=134): HLA-B27 positive (Chi-square, df, 24.98, 4) (p<0.0001); 6) SIJ+HIP-Chronic group (N=72, AS=40) vs SIJ-Chronic+HIP-Active/Chronic group (N=228, AS=144): Pat. Global (p<0.05), ESR (p<0.05). Conclusion: Hip joint lesion are closely related to sacroiliac joint lesion and HLA-B27 positive in AS. Hip pain is the main clinical manifestation of hip joint lesion in AS. Hip joint lesion may lead to function declines, disease activity in AS. References: [1]Vander C B, Munoz-Gomariz E, Font P, et al. Hip involvement in ankylosing spondylitis:epidemiology and risk factors associated with hip replacement surgery[J]. Rheumatology (Oxford), 2010, 49(1):73-81. [2]Sieper J, Rudwaleit M, Baraliakos X, et al. The Assessment of SpondyloArthritis international Society (ASAS) handbook: a guide to assess spondyloarthritis[J]. Ann Rheum Dis, 2009, 68 Suppl 2:i1-i44. [3]Ward M M, Deodhar A, Akl E A, et al. American College of Rheumatology/Spondylitis Association of America/Spondyloarthritis Research and Treatment Network 2015 Recommendations for the Treatment of Ankylosing Spondylitis and Nonradiographic Axial Spondyloarthritis[J]. Arthritis Rheumatol, 2016, 68(2):282-298. Disclosure of Interests: Qing Han: None declared, Zhaohui Zheng: None declared, Kui Zhang: None declared, Zheng Yu: None declared, Fengfan Yang: None declared, Qiang Liang: None declared, Ping Zhu: None declared, Xenofon Baraliakos Grant/research support from: Grant/research support from: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Consultant of: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Speakers bureau: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen